Syrians' Awareness of Cardiovascular Disease Risk Factors and Warning Signs: A Cross Sectional Study - Sarya Swed; Hidar Alibrahim; Haidara Bohsas; Mohammed Amir Rais; Sheikh Shoib; Anas Alali; Mohamed Abdelnasser; Hadeel Fuad Alwan Alsharjabi; Bisher Sawaf (University Library System, University of Pittsburgh, 2022)
Background: An estimated 17.8 million lives were lost in 2017 due to cardiovascular disease (CVD), resulting in a total of 330 million years of life lost and an additional 35.6 million years of disability. Numerous studies have shown the importance of education and awareness in promoting positive and long-lasting behavioral changes. This study aims to assess Syrians' awareness of cardiovascular disease (CVD) warning symptoms and risk factors and investigate further into the variables that contribute to this awareness.    Methods: A cross-sectional survey was undertaken online between August 1 and 25, 2022, to examine Syrian individuals' awareness of cardiovascular disease risk factors and early warning signs. The study's questionnaire was constructed based on prior research, and the inclusion criteria for the sample were citizens of Syria over the age of 18 who currently reside in Syria. There were three categories of questions on the questionnaire: sociodemographics, an evaluation of CVD knowledge using both open- and closed-ended inquiries, and medical history and behavioral risk factors.   Results: There were 1201 inquired participants; 728 (60.6%) were males, and 473 (39.5%) were females. Concerns about developing diabetes were reported by 45.8% (n=550), hypertension was feared by 54.0% (n=540), and 43.9% (n=572) of individuals, and heart disease was feared by 45.9% (n=572). The internet and social media platforms were the most common ways they learned about it. Closed-ended questions indicated that the majority of participants (n=1164, 94.9%) had recognized CVD risk factors, with smoking (95.2%), obesity (93.6%), cholesterol (91%), and hypertension (90.3%) being the most often reported risk factors. Close-ended questions regarding CVD warning indicators revealed that most participants (n=897, 74.7%) correctly identified the warning symptoms. However, in response to open-ended questions, most participants (n=478, 39.8%) did not identify CVD risk factors, as well only (n=291, 24.2%) did. In addition, open-ended questions concerning CVD warning signs indicated that more than half of the participants (n=680, 56.6%) had poor identification of the warning symptoms. The age group between 55 and 64 years had the greatest CVD risk factors, and education was related to greater knowledge of CVD risk factors (P-value<0.001). Males have a greater understanding of CVD risk factors than females, and married individuals have a greater understanding of CVD warning signals than those with other marital statuses. Country-dwelling individuals are less knowledgeable about CVD risk factors and warning symptoms than city-dwelling participants.    Conclusion: According to our results, there is inadequate knowledge of the risk factors and warning signs of CVDs, which contribute to the development of this illness and result in life-threatening circumstances. Consequently, there is a larger need to raise CVD awareness and learning initiatives on the disease's risk factors and symptoms. It may be able to reduce the number of advanced instances of this illness by educating individuals about the hazards of smoking and alcohol intake and by considering the family history of these CVDs.